Assistance of The Farmer Group Named Suko Makmur in Controlling of The Brown Planthopper (Nilarvata LugenStal) in Kamulyan Village, Kuwarasan Sub-District, Kebumen Regency - Wulansari, Nur Kholida; Windriyati, Ratna Dwi Hirma; Kurniawati, Ari (Khadimul Ummah, 2022)
Rice is the staple food of Indonesian people. Kebumen is one of the regencies in Indonesia that produce 7.92 tons of rice ha-1. However, in the cultivation process, a farmer group in Kamulyan village named Suko Makmur faced many obstacles, including the brown planthopper. To reduce the resistance of the pest causing pest explosion, a preventive action called The Integrated Pest Management Farmer Field School was conducted (SL-PHT). The method of SL-PHT included sharing knowledge through counseling, training for the propagation of fungal isolates (Mettarhizium spp and Beauveria bassiana), and practicing integrated pest control. The results of this activity were that the farmers can understand the main point of agroecosystem management and sustainable land management. Moreover, the farmers capable of being independent in making bio-pesticide derived from Mettarhizium spp and Beauveria bassiana. The farmers also capable of pest management using bio-insecticide.